Levels of selective oxidative stress markers and antioxidant enzymes in blood of Hubble-Bubble smokers - Shafagoj, Yanal; Al-Qudah, Tamara; Al-Essa, Mohamed K.; Mustafa, Ebtihal; Albdour, Suzan; ALkhateeb, Mohammed; Naif Karadsheh; Khatib, Faisal; Ahram, Mamoun; Mohammed, Faisal I. (Jordan Medical Journal, 2023)
Background: Hubble-Bubble smoking is a common smoking practice and spreading fast among young adults even in western countries. People think it is less toxic than cigarette smoking. Aim: The aim of this study was to investigate the levels of oxidative stress markers and antioxidants in the blood of Hubble-Bubble (smokers compared to controls as a sign of toxicity, since disease process is caused by abnormal antioxidant capacity. Methods: Blood samples were collected by authorized personnel from recruited healthy volunteers (28 habitual Hubble-Bubble smokers and 18 nonsmokers). The levels of oxidative stress markers (Malondialdehyde (MDA), and protein carbonyl) and antioxidants superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)) and lipids were measured. Results: Protein carbonyl level in HB smokers’ group (2.58 mmol/gm of protein) was significantly higher than in control group (2.58 ±0.8 vs. 2.04 ±0.8 mmol/gm of protein). While CAT level in HB smokers’ group was significantly lower than the control group (22545.4±504 vs 24772.0±344.6 mU/ml). Also, a clear difference for GPx level was found between study groups (1091.6±122 vs. 3144.9± 409mU/ml). However, no significant differences were observed between the two groups regarding the SOD and MDA levels as well as the lipids concentration. Conclusions: HB smoking is associated with increased levels of carbonyl proteins and decreased levels of catalase, and glutathione peroxidase in the plasma, which might contribute to the several adverse health effects associated with HB smoking.